2019
DOI: 10.3390/molecules24203802
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Annulations to Interesting Novel Pyrrolo[3,2-c]carbazoles

Abstract: Herein we report a significant, valuable extension of a recently implemented pyrrole benzannulation methodology that, employing versatile nitrodienes from our lab as useful C4 building blocks, led to indole derivatives characterized by unusual patterns of substitution. The 6-nitro-7-arylindoles resulting from suitably derivatized, non-symmetric dienes are of foreseeable synthetic interest in search for new polyheterocyclic systems. As an example, pyrrolocarbazoles with a rarely reported ring fusion were synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In the same year, Benzi et al synthesised pyrrolo[3,2-c]carbazoles via classical Cadogan reaction by exploring the pyrrole-to-indole benzannulation method. [27] This method was possible only due to the easy reduction of the nitro group present in the substrate 27. Here, various 7-aryl-6-nitroindoles (27) were subjected to classical Cadogan conditions consisting of the use of triethyl phosphite under reflux to get pyrrolo[3,2-c]carbazoles 28 in good yield as shown in Scheme 5.…”
Section: Formation Of Carbazole Moietymentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, Benzi et al synthesised pyrrolo[3,2-c]carbazoles via classical Cadogan reaction by exploring the pyrrole-to-indole benzannulation method. [27] This method was possible only due to the easy reduction of the nitro group present in the substrate 27. Here, various 7-aryl-6-nitroindoles (27) were subjected to classical Cadogan conditions consisting of the use of triethyl phosphite under reflux to get pyrrolo[3,2-c]carbazoles 28 in good yield as shown in Scheme 5.…”
Section: Formation Of Carbazole Moietymentioning
confidence: 99%
“…[27] This method was possible only due to the easy reduction of the nitro group present in the substrate 27. Here, various 7-aryl-6-nitroindoles (27) were subjected to classical Cadogan conditions consisting of the use of triethyl phosphite under reflux to get pyrrolo[3,2-c]carbazoles 28 in good yield as shown in Scheme 5. The authors suggested these molecules could help in the synthesis of polyheterocyclic systems with diverse applications.…”
Section: Formation Of Carbazole Moietymentioning
confidence: 99%
“…The synthesis and characterization of compounds 1-3 [21], 4 and 5 [22], and 6-8 [23] has already been reported; details are provided in Scheme 1 below. treated with the tested compound.…”
Section: Chemistrymentioning
confidence: 99%
“…Although structurally different, compounds 1-8 share a synthetic protocol whereby a nitrobutadiene (12)(13)(14), deriving from the initial ring-opening of a suitably substituted 3-nitrothiophene ( 9) [33][34][35], acts as a benzannulating agent towards indole [21], pyrrole [22], or 2-aminopyridine [23] (Scheme 1). Scheme 1.…”
Section: Chemistrymentioning
confidence: 99%
“…As a matter of fact, starting from a pioneering report [ 32 ], during our previous studies, while exploring the reactivity of different nucleophiles towards nitrobutadienes generated by an initial ring-opening of nitrothiophenes [ 33 , 34 , 35 ], we obtained a great variety of nitrogen-containing heterocycles, such as methyleneazetidines [ 36 ], pyrroles [ 37 ], pyrazoles [ 38 ], carbazoles [ 39 ], imidazo[1,2- a ]pyridines [ 40 ], and nitroindoles [ 41 ]. However, the involvement of nucleophiles able to generate O-heterocycles, as, for instance, enols, has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%